2005
DOI: 10.1088/0029-5515/45/8/002
|View full text |Cite
|
Sign up to set email alerts
|

RF current distribution and topology of RF sheath potentials in front of ICRF antennae

Abstract: The 2D (radial/poloidal) spatial topology of RF-induced convective cells developing radially in front of ion cyclotron range of frequency (ICRF) antennae is investigated, in relation to the spatial distribution of RF currents over the metallic structure of the antenna. This is done via a Green's function, determined from the ICRF wave coupling equations, and well-suited to open field lines extending toroidally far away on both sides of the antenna. Using such formalism, combined with a full-wave calculation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 27 publications
6
63
0
Order By: Relevance
“…This implies a modification of density in front of the antennas by ICRF power [5] which could be attributed to convective cells [19,20]. The spectroscopic observations of the increased Be sputtering at the limiters are consistent with the spatial sputtering patterns moving in accordance with magnetic field connections to active ICRF antennas.…”
Section: Role Of Sheath Effectsmentioning
confidence: 63%
“…This implies a modification of density in front of the antennas by ICRF power [5] which could be attributed to convective cells [19,20]. The spectroscopic observations of the increased Be sputtering at the limiters are consistent with the spatial sputtering patterns moving in accordance with magnetic field connections to active ICRF antennas.…”
Section: Role Of Sheath Effectsmentioning
confidence: 63%
“…This procedure, although clearly not self-consistent, was widely implemented as the only tool able to model realistic wave-launching structures. [5][6][7][8][9][10][11][12][13][14][15] It was shown to reproduce qualitatively some RF-induced SOL modifications observed around powered antennae. 6,8,10,11,16 Yet its quantitative validity is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…6 In previous works to decrease impurity generation during ICH, a low-Z coating on plasma-facing components, 7 reducing the sheath potential by the antenna phase, 8 decreasing the inductive imaginary current on the Faraday screen (FS) caused by misalignment 9 and rotating the center conductor 10 to a magnetic field line (MFL) have been attempted, and a favorable ICH with low impurity generation and relatively high heating efficiency was achieved with a phasing dipole. [11][12][13][14] It has been reported that field alignment for the ICRF antenna should theoretically decrease the average RF sheath potential along magnetic field lines in the Alcator C-Mod, 15 and that low-impurity production is achieved by dipole phasing using a field-aligned ICRF antenna. 16 In steady-state operation, dipole phasing may, indeed, be one of the candidate methods for decreasing impurity generation during ICH, and a toroidal phasing experiment was planned to execute a stable steady-state plasma using a field-aligned ICRF antenna in the LHD.…”
Section: à3mentioning
confidence: 99%